Krzysztof Kieslowski's Three Colors . - Kieslowski, Krzysztof (New York, NY Miramax, 2003)
Blue: Praised as one of the top films of the year by critics and audiences alike, this stylish and provocative mystery delivers captivating performances and stunning imagery! Academy Award winner Juliette Binoche (The English Patient, Best Supporting Actress; Chocolat) is a young woman left devastated by the unexpected death of her husband and child. She retreats from the world around her, but is soon reluctantly drawn into an ever-widening web of lies and passion as the dark, secret life of her husband begins to unravel. With each startling discovery and heart-stopping surprise, Blue is sure to entertain you from beginning to end. White: A seductive story of love and obsession, White won nationwide critical acclaim for its intoxicating blend of eroticism and intrigue. Directed by acclaimed director Krzysztof Kieslowski (Blue, Red, The Double Life of Veronique) and featuring sexy Julie Delpy (TV's ER, Investigating Sex, The Three Musketeers), White is the mysterious tale of a man whose life disintegrates when his beautiful wife of six months deserts him, Forced to begin anew, he rebuilds his life, only to plan a dangerous scheme of vengeance against her! Winner of the Best Director Award at the Berlin Film Fectival, White is a story of dark, illicit passions - one of the year's most provocative big-screen releases! Red: Praised by critics nationwide as one of the year's 10 best films, Red is a seductive story of forbidden love - and the unknowable mystery of coincidence. The final chapter in Krzysztoz Kieslowski's acclaimed "Three Colors" trilogy, Red stars sexy Irene Jacob (Victory, My Life So Far) as a young model whose chance meeting with an unusual stranger leads her down a path of intrigue and secrecy. As her knowledge of the man deepens, she discovers an astonishing link between his past... and her destiny! Academy Award nominated for writing, direction and cinematography, Red is Kieslowski's crowning achievement - a fascinating mystery sure to dazzle and entertain! -Cover
Disc One: Feature film: Blue Bonus features: - Reflections on Blue (Featurette) - A discussion on Kieslowski's early years - Conversation with Juliette Bionche on Kieslowski - Audio commentary with Annette Insdorf - Krzysztof Kieslowski's cinema lesson - Martin Karmitz interview with selected scenes commentary - Juliette Bionche selected scenes commen - Jacques Witta interview/commentary - Kieslowski student film: Concert of Wishes - Kieslowski Filmography Disc Two: Feature film: White Bonus features: - A look at Blanc - A discussion on Kieslowski's later years - A discussion on working with Kieslowski - A conversation with Julie Delpy on Kieslowski - Krzysztof Kieslowski's cinema lesson - Audio commentary with Annette Insdorf - Martin Karmitz interview with selected scenes commentary - Behind the scenes of White with Krzysztof Kieslowski - Kieslowski student film: Trolley - Kieslowski student film: The Face - Kieslowski student film: The Office - Kieslowski Filmography Disc Three: Feature film: Red Bonus features: - Insights into Trois Couleurs - Rouge - A conversation with Irene Jacob on Kieslowski - Audio commentary with Annette Insdorf - Krzysztof Kieslowski's cinema lesson - Martin Karmitz interview - Irene Jacob selected scenes commentary - Behind the scenes of Red with Krzysztof Kieslowski - Jacques Witta interview/commentary - Kieslowski filmography - Red at Cannes 1994
Fiction Dual-Layer Region 1 Widescreen Digitally mastered English subtitles Blue: France | Poland | Switzerland - 1993 French, Romanian and Polish Run-time: 98 minutes White: France | Poland | Switzerland - 1994 French and Polish Run-time: 92 minutes Red: France | Poland | Switzerland - 1994 French Run-time: 99 minutes